The prevalence of Candida albicans in complete denture and removable partial denture wearers: a comparative study. - (:unkn) unknown (My University, 1992)
In this study, 60 complete denture wearers, 53 removable partial denture wearers and 50 dentate subjects were examined to determine the Candidal carrier state. The influence of local factors such as denture type, smoking habits and sex on Candidal carrier rate were investigated. Wearing complete or removable partial denture was determined as an important factor increasing Candidal carrier rate. Cigarette smoking is another factor which increases Candidal growth in complete denture and removable partial denture wearers. In contrast to denture wearers Candidal carrier rate was considerably less on dentate smokers. Candidal colonization rate was found to be higher on the dorsum of the tongue. This suggests that the tongue is the primary oral reservoir of Candida albicans in the mouth.